Breaking Gender Stereotypes in STEM Through Beauty Advertising: A Semiotic Analysis: - Perangin-angin, Alemina; Bacas, Chintami Angelica; Putri, Citra Anggia; Zurriyati, Zurriyati (Talenta Publisher, 2025)
The OLAY advertisement shows the challenges that women still face in STEM fields, such as discrimination and negative stereotypes about their competencies. This study aims to explore how the advertisement uses communication strategies to support women’s empowerment and change how people see gender issues. It also examines how brands can influence shifts in public views on gender roles. This research uses a qualitative content analysis method, with data taken from OLAY India’s 2022 YouTube advertisement. The data were collected by observing scenes that show gender inequality, taking screenshots, and analyzing them using Roland Barthes’ semiotic theory: denotation, connotation, and myth. Semiotic signs are found in OLAY advertisements, both visually through the scenes in the video and verbally through the narrative and text displayed. This study shows that OLAY advertisements contain visual and verbal signs that represent the challenges faced by women in STEM fields and how they strive to fight gender stereotypes and inequalities. The findings of this study suggest that advertising can be an effective medium for promoting gender equality and changing society’s perception of women's traditional roles.